Programa Nacional de Incentivo a Mudanças Curriculares no Curso de Medicina: a experiência da UFG. - VELOSO, Tereza Christina Mertens Aguiar (2008)
Integrated to the Research Line State and Educational Policy, this study is about the Reorientation Policy of the university course in the Health Area, of the Health and Education Ministries, focusing on the National Program of Encouragement to Curricular Changes in the Medicine Course (PROMED), seeking to analyze the impact of the program on the Medicine course of the UFG. The research, which is a case study, worked with the field and habitus concept of Pierre Bourdieu as a referential of analysis in the organization and understanding of the data, obtained from documental sources and semi-structured interviews, with participants from PROMED. Concerning the implementation of the Program at the School of Medicine, the indication is that the habitus of the training of medical doctors is manifested through resistance from a part of the faculty to the transformation process in the training of medical doctors, determinant for the College to innovate in some areas and in others simply make changes. It emphasizes the pedagogical training of the faculty and of tutors in the public health system among the strategies of the Program, recognizing the importance of the participation of these agents in the process of change in the training of future medical doctors. The conclusion points to the changes in the medical formation as a process, that transcend the control of PROMED, even though the induction of changes in the course was already given and also a discussion on the institution responsibility regarding the Health Policies